Effect of body anthropometrics on brain structure of offspring of parents with bipolar disorder. (May 2020) - Subramaniapillai, Mehala; Mansur, Rodrigo B.; Chen, Yan; Lipsitz, Orly; McIntyre, Roger S.; Brietzke, Elisa; Lu, Weicong; Miao, Qingzhe; Gao, Yanling; Chen, Kun; Bi, Yanan; Zheng, Wenjing; et al.
Abstract: Background: Offspring of individuals with bipolar disorder (BD) are at greater risk for developing BD. Adiponectin (ADP), a hormone produced by adipocytes, plays a central role in energy homeostasis, insulin sensitivity and inflammatory response. ADP is negatively correlated with Body Mass Index (BMI) and is abnormal in patients with BD. Understanding the role of ADP among these offspring may help identify those likely to develop BD. The primary objective of this paper was to compare ADP levels among offspring of individuals with BD (symptomatic [SO], and asymptomatic [AO]) to offspring of healthy parents (HC). The role of ADP on cognition and ROI-based gray matter values in SO and AO offspring was secondarily assessed and compared to HC. Methods: A cross-sectional study was conducted in China by the Guangzhou Brain Hospital in offspring of individuals with and without BD. Participants underwent neuropsychiatric and cognitive assessments, MRI scans and blood analyses. BMI z-scores (zBMI) were calculated adjusting for age and gender. Results: Analyses included 117 participants (HC = 48, AO = 36, SO = 33). No significant differences were observed in plasma levels of ADP optical density (OD) among HC, AO and SO participants. No significant interaction effects on cognition were observed between symptomatic status and ADP OD, symptomatic status and BMI z-score, nor symptomatic status, zBMI and ADP OD. Multivariate tests revealed a significant interaction between offspring symptomatic status, ADP OD, and zBMI on gray matter volume in the right cerebellum ( p  = 0.05). Conclusion: These findings suggest that an interaction exists between BMI and CNS structure.